Changes in Carotid Intimal Medial Thickness (CIMT) With Glycaemic Control in Patients of T2DM - Sud, Dr. Sanjay (International Journal of Innovative Research in Medical Science, 2019)
A real world long term (10 years) prospective randomized observational study to monitor changes in CIMT of T2DM patients who achieved the target glycaemic goal of HbA1c ≤ 7%, with those who did not achieve it. CIMT is a marker of subclinical atherosclerosis associated with CVD risk factors. Hence any progression or regression of CIMT could be considered as increased or decreased risk of CVD as the case might be. This study was to ascertain if (keeping all other risk factors under control and at par in each group) a good glycaemic control could lead to a lower CIMT – leading to a lowering of CVD risk The inclusion criteria was Non – pregnant Adults (Age >18 years) T2DM with HbA1c ≥ 8% at recruitment Those who remained normotensive (B.P. ≤130/80 mm of Hg) Those who maintained a normal Lipid profile Those who had eGFR ≥ 60mL /min/1.73m2(CKD-EPI) CIMT measurements done at recruitment and then once every year Exclusions Any requirement for hospitalization throughout the entire 10 year duration The total number of patients who completed the follow up for the full ten years was 62. CIMT of the CCAs were scanned with 7-10 MHz linear probe transducer under real time B mode imaging. The patients included in the study were divided into (Group A n = 32 and Group B n = 30) Group A were those who could achieve the glycaemic target of HbA1c ≤ 7% by the end of the first year and were able to maintain the target for the major duration of the study. Group B were those who did not achieve the glycaemic target of HbA1c ≤ 7% by the end of the first year of the study and had an average HbA1c of ≥ 7.5% for the major duration of the study Results: The data at the end of ten year follow up showed that patients from Group A had a mean CIMT of 0.79 mm at baseline and at the end of the study it was 0.75 mm Group B had a mean CIMT of 0.81 mm at baseline at baseline and at the end of study period was 1.17 mm. (p<0.05) A good glycaemic control can reduce the burden of CVD as an independent entity.